DEMAND FOR GOVERNMENT SPENDING: DO OUR BELIEFS ABOUT PUBLIC DEBT MATTER? - STANCEA, Andreea; CIOCIRLAN, Cecilia (Studia Universitatis Babeș-Bolyai Oeconomica, 2023)
Macroeconomic expectations play a major role in predicting individual choices and behavior. This paper examines the effects of public debt expectations and knowledge on demand for government spending measured by individual preferences. Using a unique survey dataset applied in Central and Eastern Europe, the results show that the most knowledgeable citizens tend to support the increase in public spending. Debt expectations also have a significant impact on public spending preferences: citizens who have negative debt expectations are less likely to support public spending increases. The results shed light on the importance of economic knowledge and information provision for shaping public attitudes about future taxation. JEL classification: D14, D91, H31, H53